2020
DOI: 10.1079/hai.2020.0006
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Humane Interactions with Animals, Empathy, and Prosocial Behavior among Children

Abstract: We investigated the relationship between empathy, prosocial behavior, and frequency of humane interactions with animals among 3 rd grade children (n = 158). We measured the frequency of humane interactions with animals via the Children’s Treatment of Animals Questionnaire ( Thompson & Gullone, 2003 ), empathy via the Bryant Index of Empathy for Children and Adolescents ( Bryant, 1982 ), and prosocial behavior via teachers’ evaluations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…The findings also suggest that having a dog/other pet ownership does not predict prosocial behaviors, again suggesting that if any relationship does exist between pet ownership and prosocial behaviors, relationship quality may be a key factor to assess (Vidović et al, 1999; Wenden et al, 2021; Wice et al, 2020). Further, contrary to what prior research has indicated (e.g., Daly & Morton, 2003; Vidović et al, 1999), we did not find significant differences between pet species and prosocial behavior.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The findings also suggest that having a dog/other pet ownership does not predict prosocial behaviors, again suggesting that if any relationship does exist between pet ownership and prosocial behaviors, relationship quality may be a key factor to assess (Vidović et al, 1999; Wenden et al, 2021; Wice et al, 2020). Further, contrary to what prior research has indicated (e.g., Daly & Morton, 2003; Vidović et al, 1999), we did not find significant differences between pet species and prosocial behavior.…”
Section: Discussionmentioning
confidence: 99%
“…This relationship has been found for pets generally, but the effect appears to be particularly strong for those living with dogs (Christian et al, 2020;Vidović et al, 1999;Wenden et al, 2021;Wice et al, 2020). Companion animals may be supportive of developing prosocial behavior in youth through practice with positive social interactions and the development of empathy, which is in-turn associated with prosocial behavior (Wice et al, 2020). Similarly, through the development of these skills, youth with pets may be less likely to engage in negative social behaviors.…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations